The Importance and Necessity of Dialogue of Civilizations: Increasing of human crisis around the world (International Journal of Scientific Research and Management (IJSRM), 2020)
The importance and necessity of dialogue among civilizations, is revealing as an undeniable need of 21th century, from one perspective, the unlimited competitions for producing ultra-advanced weapons, seriously threaten the global peace, but fortunately from other viewpoint, the modern technology could prepare unprecedented opportunities for launching and continuity of dialogue in different levels. The biggest steps toward a better and more peaceful world will be taken up, when the rationality be the supporter of important decisions and the argument replace the violent emotions. In ancient theology and philosophy, human being has known as the rational animal, who has the ability of thinking and expression of what he/she thinks, this distinctive characteristic has recognized as the main character of human which shows the mentality of human being basically different and transcendental, comparing to other animals on the earth.